Preparation method of carbon-supported palladium ruthenium hydrogen evolution catalyst

The carbon-supported Pd-Ru catalyst prepared by two-step high-temperature calcination and cyclic voltammetry treatment method solves the problems of high catalyst preparation cost and unstable catalytic performance in the prior art, and achieves higher hydrogen evolution catalytic activity and lower preparation cost.

CN119753743APending Publication Date: 2025-04-04HEBEI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411959145.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, the prepared catalyst is costly and has unstable catalytic performance, which limits its industrial application in the field of hydroxide fuel cells.

Method used

A carbon-supported hydrogen evolution catalyst containing palladium and ruthenium was prepared by two-step process of high-temperature calcination and cyclic voltammetry. The method includes calcining the ruthenium dioxide hydrate, palladium oxide and graphite at high temperature, followed by cyclic voltammetry treatment in the trioelectrode system to obtain a carbon-supported Pd-Ru catalyst.

Benefits of technology

The catalyst showed higher catalytic activity than pure platinum and opened up new ideas for the recycling of ruthenium dioxide, reducing preparation costs and improving catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753743A_ABST
    Figure CN119753743A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a carbon-supported palladium ruthenium hydrogen evolution catalyst. Comprising the following steps: weighing ruthenium dioxide hydrate and palladium oxide according to a mass ratio of (15-8): 1, then adding 0.4 g of graphite, grinding, pressing into sheets, and calcining in a muffle furnace in an air atmosphere of 500-800 DEG C for 1-3 hours to obtain a precursor; the preparation method comprises the following steps: preparing a glassy carbon electrode coated with a precursor, and then carrying out cyclic voltammetry treatment in a certain voltage range and a certain scanning speed range by using a three-electrode system to obtain the carbon-loaded palladium-ruthenium hydrogen evolution catalyst. The invention provides a novel hydrogen evolution catalyst, opens up a new thought for cyclic utilization of waste ruthenium dioxide, and has potential commercial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalytic materials, and in particular to a method for preparing a carbon-supported hydrogen evolution catalyst containing palladium and ruthenium. Background Art

[0002] Hydrogen-oxygen fuel cells are batteries that use hydrogen as a reducing agent and oxygen as an oxidant to convert chemical energy into electrical energy through a chemical reaction between hydrogen and oxygen. This type of battery has the advantages of high conversion efficiency, large capacity, high specific energy, wide power range, and no need for charging, and plays an irreplaceable role in the field of energy conversion and storage. Oxygen can be obtained directly from the air at a low cost. Therefore, how to efficiently obtain ultra-pure hydrogen has become one of the bottlenecks restricting the commercial development of hydrogen-oxygen fuel cells. In recent years, with the rapid development of wind and solar energy, there has gradually emerged a situation of excess electricity that cannot be connected to the grid. Therefore, using the electricity converted from wind and solar energy to further electrolyze water to produce hydrogen has become the only way to achieve excess electricity conversion and further promote the development of hydrogen-oxygen fuel cells. In this way, in the process of electrolyzing water to produce hydrogen, an efficient hydrogen evolution catalyst is particularly important. Platinum (Pt) and its alloys are regarded as the best catalysts for electrolyzing water to produce hydrogen. However, the natural platinum resources are limited and expensive, and these shortcomings greatly limit its further application in the field of hydrogen-oxygen fuel cells. Therefore, the development of Pt-free or Pt-based binary and ternary catalysts has become one of the current research hotspots. At the same time, in industry, ruthenium dioxide (RuO2) has been widely used as an oxygen evolution catalyst for electrolyzing water to produce oxygen, and the technology is quite mature. Studies have shown that ruthenium (Ru) has similar hydrogen binding ability to Pt, and its price is much lower than Pt. This feature makes Ru-based catalysts also show great application prospects in the field of hydrogen evolution catalysts.

[0003] The prior art has reported the preparation of new catalysts by doping ruthenium dioxide. For example, Wei Hehe et al. (CN116905016A) used ruthenium trichloride solution and manganese acetylacetonate as raw materials to prepare a manganese-doped ruthenium dioxide electrocatalyst. Tian Xinlong et al. (CN117987865A) mixed a cerium source and a ruthenium source to prepare a cerium-doped ruthenium dioxide electrocatalyst. Ye et al. added Ru(NH3)6Cl3 to an aqueous solution of graphene oxide and prepared a high-performance electrocatalyst of ruthenium nanoclusters supported by nitrogen-doped graphene by hydrolysis and high-temperature reduction. Zhang et al. used RuCl3·xH2O as a ruthenium source and synthesized a new Ru catalyst by a hydrothermal method. However, the disadvantage is that the catalysts prepared by the above-mentioned prior art have a high preparation cost and unstable catalytic performance, which is not conducive to industrial application. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a carbon-supported palladium-ruthenium hydrogen evolution catalyst.

[0005] The concept of the present invention is as follows: firstly, amorphous ruthenium dioxide hydrate, anhydrous palladium oxide (PdO) and graphite are calcined at high temperature, and then the obtained precursor is subjected to cyclic voltammetry in a three-electrode system, and finally a carbon-supported palladium and ruthenium-containing hydrogen evolution catalyst is obtained. The catalyst showed excellent hydrogen evolution catalysis compared with pure platinum electrode.

[0006] Specifically, the present invention comprises the following steps: Step 1: Material preparation Ruthenium dioxide hydrate, palladium oxide (PdO), graphite, glassy carbon electrode, platinum disk electrode, graphite rod, Hg / HgO reference electrode, 1 mol L-1 KOH electrolyte; Step 2: Catalyst preparation (1) High temperature calcination 80-100 mg of ruthenium dioxide hydrate and 6-10 mg of PdO are put into a mortar, wherein the mass ratio of ruthenium dioxide hydrate to PdO is (15-8):1, and ground for 15-25 minutes, then 0.4 g of graphite is added, and the grinding is continued for 15 minutes; thereafter, the obtained mixture is pressed into tablets using a tablet press, and then the obtained tablets are transferred to a muffle furnace and calcined in air at 500°C-800°C for 1-3 hours to obtain a precursor; As a preferred condition, the optimal mass ratio of ruthenium dioxide hydrate to PdO is 10:1.

[0007] As a preferred condition, the pressed tablets are calcined in a muffle furnace in air at a temperature of 800° C. for 1 hour.

[0008] (2) Cyclic voltammetry treatment First, a working electrode coated with the above-mentioned precursor was prepared: 3-5 mg of the above-prepared precursor was transferred to 1 mL of Nafion (perfluorosulfonic acid polymer) solution, and a suspension was obtained after ultrasonic treatment for 30 minutes. Subsequently, 5 μL-10 μL of the suspension was transferred to a glassy carbon electrode using a pipette. After natural drying, a working electrode coated with the precursor was prepared. After that, cyclic voltammetry was performed using a CHI 660B electrochemical workstation, that is, a glassy carbon electrode coated with the precursor was used as the working electrode, a graphite rod was used as the counter electrode, Hg / HgO was used as the reference electrode, and 1 mol L-1 KOH was used as the electrolyte to construct a classic three-electrode system, and the potential scan rate was set to 50-100 mV. s-1, in the voltage range of 0V to -1.15V, cyclic scanning was performed for 500 to 1000 cycles, after which the working electrode was taken out and soaked in double distilled water for 1 hour, the electrode was taken out, the black powder was scraped off the working electrode, washed and dried, and a carbon-supported palladium and ruthenium-containing hydrogen evolution catalyst (denoted as Pd-Ru / C) was obtained; For cyclic voltammetry, as the optimal conditions, the potential scan rate was set to 100 mV s-1 and the cycle scan was 600 cycles.

[0009] Step 3: Catalyst hydrogen evolution performance test 2 mg of the catalyst prepared above was dissolved in 0.5 mL of Nafion solution, and a suspension was obtained after ultrasonic treatment for 30 min. Subsequently, 8 μL of the suspension was transferred to the glassy carbon electrode using a pipette. After natural drying, a glassy carbon electrode coated with the catalyst was prepared. This electrode was used as the working electrode, a graphite rod was used as the counter electrode, Hg / HgO was used as the reference electrode, and 1 mol L-1 of KOH was used as the electrolyte to construct a classic three-electrode system. The CHI 660B electrochemical workstation was connected, and the linear sweep voltammetry method was selected. The scan rate was set to 5 mV s-1, and the hydrogen evolution test was performed in the range of -0.2 V to -1.3 V to obtain the hydrogen evolution curve. After that, the voltage corresponding to the current density of 10 mA cm-2 in the hydrogen evolution curve was selected as the center, and the voltage and the corresponding current were selected within the range of ±50 mV of this center to draw the Tafel curve, where the voltage value was corrected according to the relationship, that is, the electrode potential reversible hydrogen electrode = the measured value of the electrode potential + 0.0592pH + 0.098, and the final Tafel slope graph was drawn. For comparison, the platinum disk electrode was used as the working electrode, and the hydrogen evolution curve and Tafel slope graph of the platinum electrode were tested under the condition that other conditions remained unchanged.

[0010] The beneficial effects achieved by the present invention are as follows: the present invention prepares a novel carbon-supported palladium-ruthenium hydrogen evolution catalyst by a two-step method of high-temperature calcination and cyclic voltammetry treatment, and the catalyst shows higher catalytic activity than pure platinum. The present invention not only invents a novel hydrogen evolution catalyst, but also opens up a new idea for the recycling of ruthenium dioxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 is the XRD pattern of the prepared catalyst.

[0012] Figure 2 is the EDS image of the prepared catalyst.

[0013] Figure 3 is the SEM image of the prepared catalyst.

[0014] Figure 4 This is the hydrogen evolution curve of the prepared catalyst in 1 mol L-1 KOH solution.

[0015] Figure 5 For the corresponding Figure 4 Tafel slope plot of . DETAILED DESCRIPTION

[0016] The following examples serve to illustrate the invention. Example 1

[0017] Weigh 100 mg of ruthenium dioxide hydrate and 10 mg of PdO into a mortar and grind them thoroughly for 20 minutes, then add 0.4 g of graphite and continue grinding for 15 minutes. Then, use a tablet press to press the obtained mixture into tablets, and then transfer the obtained tablets to a muffle furnace and calcine them in an air atmosphere at 800°C for 1 hour to obtain a precursor. Then, prepare a working electrode coated with the above precursor, that is, transfer 5 mg of the prepared precursor to 1 mL of Nafion solution, and obtain a suspension after ultrasonication for 30 minutes. Then, use a pipette to transfer 10 μL of this suspension and drop it on the glassy carbon electrode. After natural drying, a working electrode coated with the precursor is prepared. Afterwards, a CHI 660B electrochemical workstation was used for cyclic voltammetry, that is, a glassy carbon electrode coated with a precursor was used as a working electrode, a graphite rod was used as a counter electrode, Hg / HgO was used as a reference electrode, and 1 molL-1 KOH was used as an electrolyte to construct a classic three-electrode system. In the voltage range of 0V to -1.15V, the scan rate was set to 100mV s-1, and the cycle was repeated for 600 times. After that, the working electrode was taken out and soaked in double distilled water for 1 hour, and then the electrode was taken out, the black powder was scraped off the working electrode, and after washing and drying, a carbon-supported palladium and ruthenium-containing hydrogen evolution catalyst (denoted as Pd-Ru / C) was obtained. The obtained catalyst was characterized by XRD, EDS and SEM, and the results are as follows: Figure 1 , Figure 2 and Figure 3 shown.

[0018] The catalytic performance of hydrogen evolution of the prepared catalyst was tested under the following conditions. 2 mg of the catalyst prepared above was dissolved in 0.5 mL of Nafion solution, and a suspension was obtained after ultrasonic treatment for 30 min. Subsequently, 8 μL of the suspension was transferred to the glassy carbon electrode using a pipette. After natural drying, a glassy carbon electrode coated with the catalyst was prepared. This electrode was used as the working electrode, a graphite rod was used as the counter electrode, Hg / HgO was used as the reference electrode, and 1 mol L-1 KOH was used as the electrolyte to construct a classic three-electrode system. Connect to the CHI 660B electrochemical workstation, select linear sweep voltammetry, set the scan rate to 5 mV s-1, and perform a hydrogen evolution test in the range of -0.2 V to -1.3 V to obtain a hydrogen evolution curve. In order to compare the hydrogen evolution performance with that of pure platinum, the glassy carbon electrode coated with the catalyst was replaced with a platinum disk electrode, and the pure platinum hydrogen evolution curve was tested. The results are shown in the figure. Figure 4 As shown. The voltage corresponding to the current density of 10 mA cm-2 in the hydrogen evolution curve is selected as the center, and the voltage and the corresponding current are selected within the range of ±50 mV of this center to draw the Tafel slope diagram. The voltage value is corrected according to the electrode potential reversible hydrogen electrode = the measured value of the electrode potential + 0.0592pH + 0.098, and the final Tafel slope diagram is drawn. The result is shown as follows Figure 5 shown.

[0019] like Figure 1As shown, in the XRD spectrum of ruthenium dioxide hydrate, an obvious broad peak appears at 2θ of 21.43°, which indicates that ruthenium dioxide hydrate has an amorphous structure. For the prepared catalyst Pd-Ru / C, in addition to an obvious broad peak at 21.43°, many sharp diffraction peaks appear, indicating that Pd-Ru / C is composed of a variety of crystalline substances. The peak at 26.76° corresponds to the (002) crystal plane of graphite (JCPDS, NO. 25-284), indicating that some graphite still exists in the prepared catalyst after high-temperature calcination. The diffraction peaks at 28.2°, 35.2°, 54.6°, 65.8°, 67.3°, and 83.4° correspond to the (110), (101), (211), (310), (112), and (321) crystal planes of RuO2 (JCPDS, NO. 21-1172), respectively, which indicates that after high-temperature calcination, part of the amorphous ruthenium dioxide hydrate has been converted into ruthenium dioxide (RuO2) with high crystallinity. Interestingly, the characteristic diffraction peaks of elemental Ru appeared in the XRD spectrum of Pd-Ru / C, namely the diffraction peaks at 2θ of 38.4°, 42.2°, 44.1°, 58.4°, 69.5°, 78.4°, 84.7° and 86.0°, which exactly correspond to the (100), (002), (101), (102), (110), (103), (112) and (201) crystal planes of elemental Ru with hexagonal crystal structure (JCPDS, NO. 6-663), which indicates that part of RuO2 has been reduced to elemental Ru by graphite during the calcination process. Careful observation shows that characteristic diffraction peaks of elemental palladium also appear in the XRD spectrum of Pd-Ru / C, that is, the diffraction peaks at 40.15°, 46.59°, 68.18°, and 82.24° correspond to the (111), (200), (220), and (311) crystal planes of face-centered cubic palladium (JCPDS, NO. 5-681), respectively, indicating that after calcination and voltammetric cycling treatment, palladium oxide has been reduced to elemental palladium. Figure 1 This shows that the prepared catalyst contains carbon, ruthenium dioxide, elemental ruthenium and elemental palladium. It is a completely new substance different from the previous metal-doped ruthenium dioxide.

[0020] Figure 2 The EDS graph of the prepared catalyst shows peaks corresponding to C, O, Ru and Pd elements, and the atomic percentages of C, O, Ru and Pd elements are 5.4%, 54.2%, 39.0% and 1.50% respectively, which indicates that the prepared catalyst is a substance containing C, O, Ru and Pd elements.

[0021] Figure 3The following are SEM images of the prepared catalyst at different scales. From the SEM image with a scale of 1 μm (the SEM image on the left), it can be seen that the surface of the prepared material is uneven, and the material is composed of numerous small particles. At the same time, careful observation shows that there are many holes of different sizes on the surface of the material. From the SEM image with a scale of 200 nm (the SEM image on the right), it can be seen that the surface of the prepared catalyst material is composed of many irregular block-shaped or strip-shaped particles tightly packed together, and there are obvious pores between aggregates of different sizes.

[0022] Figure 4 The hydrogen evolution curves of the prepared catalysts Pd-Ru / C and pure platinum are shown. The curves were tested on a CHI 660B electrochemical workstation with a glassy carbon electrode coated with a catalyst as the working electrode, a graphite rod as the counter electrode, Hg / HgO as the reference electrode, 1 molL-1 KOH as the electrolyte, and a scan rate of 5 mV s-1. It can be seen from the figure that the overpotential required for the catalyst Pd-Ru / C to reach a current density of 10mA cm-2 is 75 mV, which is significantly lower than the overpotential on the pure platinum electrode (138 mV). This shows that the prepared catalyst has higher hydrogen evolution catalytic performance than pure platinum.

[0023] Figure 5 Based on Figure 4 The Tafel slope plotted. As can be seen from the figure, the Tafel slopes of the prepared catalyst and pure platinum electrode are 92.08 mV dec-1 and 177.76 mV dec-1, respectively. The lower the Tafel slope, the lower the overpotential required to increase the same current, that is, compared with pure platinum, the prepared catalyst Pd-Ru / C has faster reaction kinetics in the hydrogen evolution reaction (HER). Example 2

[0024] Weigh 100 mg of ruthenium dioxide hydrate and 9 mg of PdO into a mortar and grind them thoroughly for 18 minutes, then add 0.4 g of graphite and continue grinding for 15 minutes. Then, use a tablet press to press the obtained mixture into tablets, then transfer the obtained tablets to a muffle furnace and calcine them in an air atmosphere at 700°C for 2 hours to obtain a precursor. Next, prepare a working electrode coated with the above precursor, that is, transfer 4 mg of the prepared precursor to 1 mL of Nafion solution, and obtain a suspension after ultrasonic treatment for 30 minutes. Then, use a pipette to transfer 6 μL of this suspension droplets to a glassy carbon electrode, and after natural drying, prepare a working electrode coated with a precursor. After that, perform cyclic voltammetry on a CHI 660B electrochemical workstation according to the method of Example 1, that is, set the scan speed to 50 mV s-1, and set the number of cycles to 900. Then, operate according to Example 1 to obtain the prepared catalyst.

[0025] Subsequently, the hydrogen evolution curve test and Tafel slope diagram were drawn according to Example 1. The results show that the overpotential required for the catalyst Pd-Ru / C to reach a current density of 10 mA cm-2 is 83 mV, which is significantly lower than the overpotential on the pure platinum electrode (138 mV). The Tafel slopes of the prepared catalyst Pd-Ru / C and the pure platinum electrode are 106 mV dec-1 and 177.8 mV dec-1, respectively. This shows that the prepared catalyst has higher hydrogen evolution catalytic performance than pure platinum. Example 3

[0026] Weigh 85 mg of ruthenium dioxide hydrate and 9 mg of PdO into a mortar and grind them thoroughly for 15 minutes, then add 0.4 g of graphite and continue grinding for 16 minutes. Then, use a tablet press to press the obtained mixture into tablets, then transfer the obtained tablets to a muffle furnace and calcine them in an air atmosphere at 750°C for 2 hours to obtain a precursor. Next, prepare a working electrode coated with the above precursor, that is, transfer 3 mg of the prepared precursor to 1 mL of Nafion solution, and obtain a suspension after ultrasonic treatment for 30 min. Then, use a pipette to transfer 5 μL of this suspension droplets to a glassy carbon electrode, and after natural drying, prepare a working electrode coated with a precursor. Afterwards, according to the method of Example 1, the scanning speed is set to 50 mV s-1 on the CHI 660B electrochemical workstation, the number of cycles is set to 700, and cyclic voltammetry treatment is performed. After that, according to Example 1, the prepared catalyst is obtained.

[0027] Subsequently, the hydrogen evolution curve was tested and the Tafel slope was plotted according to Example 1. The results show that the overpotential required for the catalyst Pd-Ru / C to reach a current density of 10 mA cm-2 is 86 mV, which is significantly lower than the overpotential on the pure platinum electrode (138 mV). The Tafel slopes of the prepared catalyst and the pure platinum electrode are 107 mV dec-1 and 177.8 mV dec-1, respectively. This shows that the prepared catalyst has higher hydrogen evolution catalytic performance than pure platinum. Example 4

[0028] Weigh 80 mg of ruthenium dioxide hydrate and 9 mg of PdO into a mortar and grind them thoroughly for 20 minutes, then add 0.4 g of graphite and continue grinding for 19 minutes. Then, use a tablet press to press the obtained mixture into tablets, then transfer the obtained tablets to a muffle furnace and calcine them in an air atmosphere at 650°C for 2 hours to obtain a precursor. Next, prepare a working electrode coated with the above precursor, that is, transfer 3 mg of the prepared precursor to 1 mL of Nafion solution, and obtain a suspension after ultrasonic treatment for 30 min. Then, use a pipette to transfer 5 μL of this suspension droplets to a glassy carbon electrode, and after natural drying, prepare a working electrode coated with a precursor. According to the method of Example 1, the scanning speed is set to 50 mV s-1 on the CHI 660B electrochemical workstation, the number of cycles is set to 800, and cyclic voltammetry treatment is performed. After that, operate according to Example 1 to obtain the prepared catalyst.

[0029] Subsequently, the hydrogen evolution curve was tested and the Tafel slope graph was drawn according to Example 1. The results show that the overpotential required for the catalyst Pd-Ru / C to reach a current density of 10 mA cm-2 is 90 mV, which is significantly lower than the overpotential on the pure platinum electrode (138 mV). The Tafel slopes of the prepared catalyst and the pure platinum electrode are 108 mV dec-1 and 177.8 mV dec-1, respectively. This shows that the prepared catalyst has higher hydrogen evolution catalytic performance than pure platinum. Example 5

[0030] Weigh 95 mg of ruthenium dioxide hydrate and 9 mg of PdO into a mortar and grind them thoroughly for 18 minutes, then add 0.4 g of graphite and continue grinding for 16 minutes. Then, use a tablet press to press the obtained mixture into tablets, then transfer the obtained tablets to a muffle furnace and calcine them in an air atmosphere at 600°C for 1.5 hours to obtain a precursor. Next, prepare a working electrode coated with the above precursor, that is, transfer 3 mg of the prepared precursor to 1 mL of Nafion solution, and obtain a suspension after ultrasonic treatment for 30 min. Then, use a pipette to transfer 8 μL of this suspension droplets to a glassy carbon electrode, and after natural drying, a working electrode coated with a precursor is prepared. Afterwards, according to the method of Example 1, the scanning speed is set to 100 mV s-1 on a CHI 660B electrochemical workstation, and the number of cycles is set to 900 cycles. Cyclic voltammetry treatment is performed, and then, according to Example 1, the prepared catalyst is obtained.

[0031] Subsequently, the hydrogen evolution curve was tested and the Tafel slope was plotted according to Example 1. The results show that the overpotential required for the catalyst Pd-Ru / C to reach a current density of 10 mA cm-2 is 83 mV, which is significantly lower than the overpotential on the pure platinum electrode (138 mV). The Tafel slopes of the prepared catalyst and the pure platinum electrode are 110 mV dec-1 and 177.8 mV dec-1, respectively. This shows that the prepared catalyst has higher hydrogen evolution catalytic performance than pure platinum. Example 6

[0032] Weigh 100 mg of ruthenium dioxide hydrate and 8 mg of PdO into a mortar and grind them thoroughly for 20 minutes, then add 0.4 g of graphite and continue grinding for 18 minutes. Then, use a tablet press to press the obtained mixture into tablets, and then transfer the obtained tablets to a muffle furnace and calcine them in an air atmosphere at 550°C for 2 hours to obtain a precursor. Next, prepare a working electrode coated with the above precursor, that is, transfer 3 mg of the prepared precursor to 1 mL of Nafion solution, and obtain a suspension after ultrasonic treatment for 30 min. Then, use a pipette to transfer 8 μL of this suspension droplets to a glassy carbon electrode, and after natural drying, prepare a working electrode coated with a precursor. Afterwards, according to the method of Example 1, the scanning speed is set to 50 mV s-1 on the CHI 660B electrochemical workstation, the number of cycles is set to 700, and cyclic voltammetry treatment is performed. After that, according to Example 1, the prepared catalyst is obtained.

[0033] Then, the hydrogen evolution curve was tested and the Tafel slope was plotted according to Example 1. The results show that the overpotential required for the catalyst Pd-Ru / C to reach a current density of 10 mA cm-2 is 86 mV, which is significantly lower than the overpotential on the pure platinum electrode (138 mV). The Tafel slopes of the prepared catalyst and the pure platinum electrode are 109 mV dec-1 and 177.8 mV dec-1, respectively. This shows that the prepared catalyst has higher hydrogen evolution catalytic performance than pure platinum.

Claims

1. A method for preparing a carbon-supported palladium-ruthenium hydrogen evolution catalyst, characterized in that The following steps are involved: Step 1: Material preparation Ruthenium dioxide hydrate, PdO, graphite, glassy carbon electrode, platinum disk electrode, graphite rod, Hg / HgO reference electrode, 1 mol L-1 KOH electrolyte; Step 2: Catalyst preparation (1) High temperature calcination 80-100 mg of ruthenium dioxide hydrate and 6-10 mg of PdO are put into a mortar, wherein the mass ratio of ruthenium dioxide hydrate to PdO is (8-15):1, and ground for 15-25 minutes, then 0.4 g of graphite is added, and grinding is continued for 15 minutes; then, the obtained mixture is pressed into tablets using a tablet press, and then the obtained tablets are transferred to a muffle furnace and calcined in an air atmosphere at 500°C-800°C for 1-3 hours to obtain a precursor; (2) Cyclic voltammetry treatment First, a working electrode coated with the above-mentioned precursor was prepared: 3-5 mg of the above-prepared precursor was transferred to 1 mL of Nafion (perfluorosulfonic acid polymer) solution, and a suspension was obtained after ultrasonic treatment for 30 minutes. Subsequently, 5-10 μL of the suspension was transferred to a glassy carbon electrode using a pipette, and the working electrode coated with the precursor was prepared after natural drying. After that, cyclic voltammetry was performed using a CHI 660B electrochemical workstation, that is, the glassy carbon electrode coated with the precursor was used as the working electrode, the graphite rod was used as the counter electrode, Hg / HgO was used as the reference electrode, and 1 mol L-1 KOH was used as the electrolyte to construct a classic three-electrode system, and the potential scan rate was set to 50-100 mV s-1, in the voltage range of 0V to -1.15V, cyclic scanning was performed for 500 to 1000 times. After that, the working electrode was taken out and soaked in double distilled water for 1 hour. The electrode was taken out and the black powder was scraped off the working electrode. After washing and drying, a carbon-supported hydrogen evolution catalyst containing palladium and ruthenium was obtained.

2. The preparation method according to claim 1, characterized in that: The mass ratio of ruthenium dioxide hydrate to PdO is 10:

1.

3. The preparation method according to claim 1, characterized in that: The pellets were calcined in a muffle furnace in an air atmosphere at a temperature of 800 °C for 1 h.

4. The preparation method according to claim 1, characterized in that: During cyclic voltammetry, the scan rate was set to 100 mVs-1 and the number of cycles was 600.

Citation Information

Patent Citations

  • Preparation method and application of manganese-doped ruthenium dioxide coated ruthenium electrocatalyst

    CN116905016A

  • Cerium-doped ruthenium dioxide electrocatalyst as well as preparation method and application thereof

    CN117987865A